The Revised Arabic Schwartz Outcome Scale-10 (SOS-10-AR). (3rd April 2021) - Aldawsari, Hussam; Laux, John M.; Dari, Tahani; Gaballa, Heba
Abstract: This study presents the Revised Arabic Schwartz Outcome Scale-10 (Blais et al., 1999 ). Data collected from Arabic and English speakers residing in the United States ( n = 152) and international Arabic speakers ( n = 423) provided robust psychometric support for the instrument's use to measure Arabic speakers' mental health outcomes.